The impact of extractable organic matter from gasoline and alternative fuel emissions on bronchial cell models (BEAS-2B, MucilAir™). (April 2022) - Sima, Michal; Cervena, Tereza; Elzeinova, Fatima; Ambroz, Antonin; Beranek, Vit; Vojtisek-Lom, Michal; Klema, Jiri; Ciganek, Miroslav; Rossner, Pavel
Abstract: Air pollution caused by road traffic has an unfavorable impact on the environment and also on human health. It has previously been shown, that complete gasoline emissions lead to toxic effects in cell models originating from human airways. Here we focused on extractable organic matter (EOM) from particulate matter, collected from gasoline emissions from fuels with different ethanol content. We performed cytotoxicity evaluation, quantification of mucin and extracellular reactive oxygen species (ROS) production, DNA breaks detection, and selected gene deregulation analysis, after one and five days of exposure of human bronchial epithelial model (BEAS-2B) and a 3D model of the human airway (MucilAir™). Our data suggest that the longer exposure had more pronounced effects on the parameters of cytotoxicity and mucin production, while the impacts on ROS generation and DNA integrity were limited. In both cell models the expression of CYP1A1 was induced, regardless of the exposure period or EOM tested. Several other genes, including FMO2, IL1A, or TNF, were deregulated depending on the exposure time. In conclusion, ethanol content in the fuels did not significantly impact the toxicity of EOM. Biological effects were mostly linked to xenobiotics metabolism and inflammatory response. BEAS-2B cells were more sensitive to the treatment. Highlights: Human bronchial epithelial cells were exposed to EOMs from gasoline emissions Longer exposure of both EOMs had a stronger effect in both cell models Only small differences in the impact on cells were detected between EOMs after exposure BEAS-2B cells were more sensitive than MucilAir™ CYP1A1 was up-regulated after the exposure of both cell models to both EOMs